Evaluation of Corruption Prevention Programs Case Study on the Corruption Prevention Network Program (JAGA) - Chrisna Adhitama Surya Nugraha; Machmudin Eka Prasetya (Jurnal Indonesia Sosial Teknologi, 2024)
Efforts to prevent corruption in the form of improving the quality of public service transparency are one of the most crucial things to be done in Indonesia. (KPK, 2023). This is carried out through the Corruption Prevention Network (Jaga) program by the KPK which aims to encourage transparency in public services and public participation in corruption prevention. Unfortunately, the program has not run well based on the assessment of respondents in the Jaga user survey because it has not reached all areas prone to corruption and the complaint resolution rate is low. This study aims to eval_uate the Jaga program and assess the suitability of the Jaga program with the Fraud Risk Management (FRM) framework. This study concludes that in general, the Jaga program is in line with the FRM framework but needs to be improved in terms of documentation of the Jaga concept, the implementation of comprehensive and periodic corruption risk assessments, the development of specific preventive controls based on the intervening public service sector, the improvement of the mechanism for handling complaints of indications of corruption, and the implementation of periodic monitoring of FRM implementation.